Moisture consumed by the winter wheat variety “Niva Stavropoliya” to produce yields with the use of biological products and fertilizers in the Don area - D. M. Repka; L. P. Beltyukov; Yu. V. Gordeeva (Зерновое хозяйство России, 2020)
The purpose of the current study was to determine the amount of moisture consumed by winter wheat to produce yields with the use of biological products and fertilizers. Under the conditions of insufficient and unstable moisture in theRostovregion, the granular mineral fertilizers applied in winter wheat cultivation caused by a moisture deficit do not always give a positive effect. In this case, in our opinion, the use of new biological products and fertilizers in a liquid form for the pre-sowing treatment of seeds and vegetative plants is a very promising direction. Thus, there have been carried out field trials to study the effect of various water-soluble fertilizers and biological products on the moisture consumption and productivity of winter wheat variety “Niva Stavropoliya” sown in fallow lands. The field trials were conducted in 2016–2018 at the AFC (SA) “Rus” of the Salsky district, located in the southern part of theRostovregion. There have been studied such biological products as “Extrasol”, “Rostok”, “Aquamix” and water-soluble fertilizers “Aquarin5”and “Aquarin9”when using optimal doses of fertilizers. The trials have shown that the combined use of biological products and water-soluble fertilizers was the most effective, when used 0.1 kg/t “Aquamix” for seed treatment + 2 kg/ha “Aquarin5”during a period of tillering + 2 kg/ha “Aquarin9”during a period of head formation together with the use of mineral fertilizers. As a result, productivity increase was 36% compared with that of the control.